Management Model Development of Instructional Materials For Professional Competence Improvement Of Teachers In Indonesia - Mashun Mashun; Mustaji Mustaji; Andi Mariono; Muhamad Suhardi (Eduvest - Journal of Universal Studies, 2022)
This study is aimed at developing a management model of web-based instructional materials that can be used by teachers to obtain teaching materials, knowledge sharing and discussions in order to improve their professional competence. This research used Borg and Gall’s theory, 4-D Model and Development Model Prototyping. The results revealed that based on the judgement of expert of educational technology, expert of web design, and expert of information systems, the model fits to be applied. The results from individual evaluation, small group test, and field test showed that 84, 00% of the web-based module can be used well. Furthermore, the results of the expert evaluation and field test indicate that the webbased module can be used by Indonesian teachers either individually or in groups and it is very helpful for learning activities